2023
DOI: 10.1038/s41398-023-02456-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psilocybin on marble burying in ICR mice: role of 5-HT1A receptors and implications for the treatment of obsessive-compulsive disorder

Abstract: Preliminary clinical findings, supported by preclinical studies employing behavioral paradigms such as marble burying, suggest that psilocybin may be effective in treating obsessive-compulsive disorder. However, the receptor mechanisms implicated in the putative anti-obsessional effect are not clear. On this background, we set out to explore (1) the role of serotonin 2A (5-HT2A) and serotonin 1A (5-HT1A) receptors in the effect of psilocybin on marble burying; (2) the effect of staggered versus bolus psilocybi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…at a volume of 10 mL/kg. Methods for drug preparation and doses of psilocybin (0.5, 1, or 2 mg/kg), WAY100635 (2 mg/kg), and MDL100907 (1 mg/kg) were chosen based on prior work 3335 .…”
Section: Methodsmentioning
confidence: 99%
“…at a volume of 10 mL/kg. Methods for drug preparation and doses of psilocybin (0.5, 1, or 2 mg/kg), WAY100635 (2 mg/kg), and MDL100907 (1 mg/kg) were chosen based on prior work 3335 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that the 5-HT1a agonism of psilocybin does not induce stimulus control, there is still evidence for the role it plays in the drug's behavioral effects, specifically with respect to the modulation of attentional control (Carter et al, 2005), compulsive behavior (Singh et al, 2023), and exploration (Halberstadt et al, 2011). The later study demonstrated that 5-HT1a agonism is likewise primarily implicated in the behavioral and phenomenological effects of 5-MeO-DMT, which is unsurprising, given the high ratio of 5-HT1a…”
Section: -Ht2a and 5-ht1a Receptor Agonism In Psychedelicsmentioning
confidence: 99%
“…Intriguingly, a 5-HT1AR antagonist reversed the drop in body temperature observed in mice after administration of psilocybin, whereas an agonist inhibited some psilocybin-induced effects in humans. 26 , 96 It is crucial to accurately differentiate between pre- and postsynaptic receptors, particularly 5-HT1AR, to capture the cellular and molecular mechanisms governing their efficacy in alleviating disease-related phenotypes associated with presynaptic 5-HT synthesis, reuptake, and release or post-synaptic structural plasticity changes related to the disease.…”
Section: What Do Psc-derived Brain Cells Bring To Psychedelic Studies?mentioning
confidence: 99%